Considerations about the welding repair effects on the structural integrity of an airframe critical to the flight-safety - Nascimento, Marcelino P. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2010)
Structures critical to the flight-safety are commonly submitted to several maintenance repairs at the welded joints in order to prolong the in-service life of aircrafts. The aim of this study is to analyze the effects of Tungsten Inert Gas (TIG) welding repair on the structural integrity of the AISI 4130 aeronautical steel by means of experimental fatigue crack growth tests in base-material, heat-affected zone (HAZ) and weld metal. The tests were performed on hot-rolled steel plate specimens, 0.89 mm thick, with load ratio R = 0.1, constant amplitude, at 10 Hz frequency and room temperature. Increase of the fracture resistance was observed in the weld metal but decreasing in the HAZ after repair. The results were associated to microhardness and microstructural changes with the welding sequence. (C) 2010 Published by Elsevier Ltd.
Keywords: AISI 4130 aeronautical steel; fatigue crack growth; TIG welding; welded joints; HAZ; aircraft motor-cradle